Analysis of the Effectiveness of the Recovery Toolkit for Storage Media Using a Criteria-Based Evaluation Approach - Purnama, Wahyu Aji; Djumhadi, Djumhadi; Servanda, Yustian; Wijayanto, Agus (Universitas Bunda Mulia, 2025)
In the rapidly developing digital era, the use of various storage media is also increasing. However, data loss can occur for various reasons, including user error in formatting storage media. Therefore, data recovery techniques become an important way to restore lost information. Thus, this study aims to compare the effectiveness of the Wondershare Recoverit and EaseUS Data data recovery toolkits in the storage media data recovery process using a criteria-based evaluation approach. This study uses the Experiment method as a stage to test the performance of both toolkits, with a focus on evaluating and comparing the effectiveness of both data recovery tools in finding the amount of data, the speed of the data recovery process, and the quality of the data that has been successfully recovered. Testing is carried out using formatted storage media to determine the level of success of the two toolkits. The results of the study will show the effectiveness of the data recovery toolkit between EaseUS Data and Wondershare Recoverit.